The influence of tributary flow density differences on the hydrodynamic behavior of a confluent meander bend and implications for flow mixing - Herrero, Horacio Sebastian Julian (2018)
The goal of this study is to evaluate the influence of tributary flow density differences on hydrodynamics and mixing at a confluent meander bend. A detailed field characterization is performed using an Acoustic Doppler Current Profiler (ADCP) for quantification of the 3D flow field, flow discharge and bathymetry, as well as CTD measurements (conductivity, temperature, depth) to characterize the patterns of mixing. Satellite images of the confluence taken at complementary times to the field surveys were analyzed to evaluate the confluence hydrodynamics at different flow conditions. The results illustrate the differences in hydrodynamics and mixing length in relation to confluences with equal density tributaries. At low-density differences, and higher discharge ratio (Qr) between the two rivers, the flow is similar to equi-density confluent meander bends. In contrast, at high-density differences (low Qr), the tributary flow is confined to near the confluence but the density difference causes the flow to move across channel. In this case, the density difference causes the lateral spread of the tributary flow to be greater than at a greater Qr when the density difference is less. These results illustrate the potential importance of density differences between tributaries in determining the rate and spatial extent of mixing and sediment dispersal at confluent meander bends.